Intersection RSU in Vanet (Global Journal of Computer Science and Technology, 2015)
Vanet is most important and new type adhoc networking which needs attention If research of scholars and technology of automobile industry combinely work in this area they can reduces accidents happening on roads Basically Vanet is Adhoc network in which vehicles are treated as Node And these nodes are communicating with each other as well as rsu Road side unit s on the road In This paper we shortly studied real time examples of vanet There is huge no of accidents happens at the intersection
Keywords: vanet; intersection Rsu; broad casting at intersection